Influence of Humidity and Carbon Dioxide on the (La0.6Sr0.4)0.99Co1-xMxO3-δ (M = Nb, Ti) Oxygen Electrode Characteristics. (10th July 2019) - Heinsaar, Alar; Kivi, Indrek; Nurk, Gunnar; Aruväli, Jaan; Lust, Enn
Abstract : Cathode material, (La0.6 Sr0.4 )0.99 CoO3-δ, is highly active for oxygen reduction process in SOFC applications. Humidity and CO2 content in the cathode compartment increase the degradation rate of the cathode. Substituting Nb and Ti into (La0.6 Sr0.4 )0.99 CoO3−δ B-site has an effect on the chemical stability of this material. Synthesized (La0.6 Sr0.4 )0.99 CoO3−δ, (La0.6 Sr0.4 )0.99 Co1-x Nbx O3−δ and (La0.6 Sr0.4 )0.99 Co1-x Tix O3−δ powders with different stoichiometry were analyzed with thermogravimetric analysis (TGA) and with X-ray diffraction method (XRD). The results obtained indicate that doping of (La0.6 Sr0.4 )0.99 CoO3−δ B-site with Nb and Ti make these materials more resilient to form unwanted compounds on the cathode surface.